Penerapan Sistem Penerangan Jalan menggunakan Tenaga Surya di Kampung Banjar, Tanjung Pinang - Muhamad Afham; Apriliansyah Apriliansyah; Cahya Nabila; Samuel Jefry Marthin; Safitri Wulandari; Muhammad Riza Mahendra; Muhammad Syukur Tri Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service initiative aimed to address the lack of street lighting in Kampung Banjar, Tanjung Pinang by implementing a solar-powered public street lighting system. The methodology included site surveys, system design, installation of components (10WP solar panels, 12V batteries, LDR sensors, and LED lights), and community training for system maintenance. The results demonstrated that the system successfully enhanced community safety and comfort by providing stable nighttime illumination, while also supporting economic and social activities. Additionally, the system proved environmentally friendly and cost-effective due to its reliance on renewable energy. This project highlights how simple solar-based technology can significantly improve the quality of life in underserved rural areas.